Mapping flood inundation areas over the lower part of the Con River basin using Sentinel 1A imagery - Thao, Nguyen Thien Phuong; Linh, Tran Tuan; Ha, Nguyen Thi Thu; Vinh, Pham Quang; Linh, Nguyen Thuy (Vietnam Journal of Earth Sciences, 2020)
This study aims to determine a processing method for rapid flood inundation and potential flood-damaged area mapping in the lower part of the Con River basin, a region most vulnerable to floods in Vietnam, using Sentinel 1A (S1A) image. A threshold from -23 dB to -12 dB of the VV band was identified for extracting the water areas from S1A image and was applied in 28 S1A scenes to identify flood dynamics. The time-series map of flood inundation areas during the period of December 2017 to December 2018 evidenced Tuy Phuoc and northern part of An Nhon as the districts most inundated by the 2017 and 2018 floods, which is consistent to the local records. The round-year trend of total flood inundation area shows strong correlations with the Con river water level (R = 0.75) and local precipitation (R = 0.64) measured in Binh Nghi hydro-meteorological station confirming the appropriateness of the study method and the capability of S1A data in monitoring floods.